When Policy Conflict Becomes a Legal Crisis: Policy Conflict Framework in Merapi Sand Mining - Laras Lingganingrum; M. Mude Sastra Atmaja (Media of Law and Sharia, 2026)
This study examines sand mining conflicts in the Mount Merapi river area as a case of escalating policy conflict that has evolved into a legal crisis. The research method used is qualitative research with a case study approach based on secondary data. This article uses the Policy Conflict Framework (PCF) as an analytical framework to identify the configuration of actors, power relations, and interaction dynamics that shape the character and intensity of policy conflicts in Merapi sand mining. The asymmetry of power between pro-mining and counter-mining actors results in communication distortions. Counter-mining actors are marginalized while pro-mining actors manage the conflict covertly, resulting in the war transforming into a governance crisis with ecological impacts and a technical crisis of legitimacy. The results of this study indicate that the Merapi mining conflict reflects a pattern of high-intensity pragmatic conflict policies, characterized by a recurring and difficult-to-resolve cycle based on an unwillingness to compromise. To break this cycle, administrative law reform, consistent law enforcement, and public participation mechanisms are needed that can balance economic interests with socio-ecological justice.